FRACTURE PROCESS ZONE IN GRANITE: A MICROSTRUCTURAL ANALYSIS - Janssen C.; Wagner F.C.; Zang A.; Dresen G. (My University, 2001)
Shear fracture propagation in rock is accompanied by localized microcracking in a process zone surrounding the fracture tip. We investigated the crack microstructures along experimentally formed shear fractures from four granite samples (uniaxial compression tests). Five transects across a macroscopic fracture were inspected optically in transmitted light. Five hundred thirty-two photomicrographs were taken from seven study areas along each transect. We determined length, width, density, and orientation of open cracks and their assignment to intra-, transgranular, or grain-boundary cracks. Crack density decreases with increasing distance to the macroscopic shear fracture and toward the fracture tip. The highest crack densities correlate with the maximum number of acoustic emissions. Most cracks enclose a small angle (0–20°) with the macroscopic shear fracture. Intragranular cracks are more abundant than transgranular and grain-boundary cracks. The number of transgranular cracks increases towards the macroscopic shear fracture, but the number of grain-boundary cracks decreases. The decrease in crack density with increasing distance to the fault is accompanied by a change from strongly preferred crack orientation in the fault core to a random crack distribution away from the fault. Fracture process zone widths range from 2.1±0.8 mm (Ag51r) to 5.6±1.9 mm (Ag18r). The ratio of process zone width to fault length is approximately 0.04–0.07. This observation agrees with observations from natural fault zones. The fracture surface energy ranges from 0.2 to 1.2 J. This corresponds to <10% of the total strain energy.